Religion and Nationalism in Shaping the Fiqh of Armed Jihad: A Lesson to the Indonesian National Counterterrorism Policy - Munajat, Munajat (Universitas Islam Negeri Jakarta, 2022)
Understanding the formulation of the fiqh of jihad is a key success in countering violent Islamist extremism and terrorism. Two salient factors that often come up in the academic discussion of the making of violent jihad are nationalism and religion. The present study investigates these two crucial related factors in the two prominent cases of armed jihad in Iran (1980-1988) and Palestina (1990-2010); and, then, how they may provide a lesson to the counterterrorism policy in Indonesia. The study uses secondary data to investigate the making of violent jihad of Iran and the Palestinian Hamas. While in the case of Indonesian policy, this article uses a government report on counterterrorism and interviews with the state counterterrorism authorities. This study shows that the interactions of two ideologies (religion and nationalism) together create a sustained and powerful force of a violent jihad by the Iranians during the Iraq-Iran War and Palestinian Hamas against Israel to achieve their political goals. In contrast to this practice, Indonesia has applied nationalism in counterterrorism policies as a strategy to deradicalize violent ideology with religious motives. This article shows that counterterrorism policies need to put more emphasis on the meaning of non-violent jihad.Keywords: religion; nationalism; jihad; counterterrorism AbstrakMemahami fikih jihad merupakan kunci keberhasilan dalam melawan ekstrimisme dan terorisme. Dua faktor yang sering muncul dalam diskusi akademis tentang pembentukkan wacana jihad kekerasan adalah nasionalisme dan agama. Studi ini menyelidiki dua faktor penting dalam kasus jihad bersenjata di Iran (1980-1988) dan Palestina (1990-2010); dan bagaimana kasus ini menjadi pertimbangan dalam kebijakan kontraterorisme di Indonesia. Studi ini menggunakan data sekunder untuk menyelidiki pembentukkan jihad kekerasan di Iran dan Hamas Palestina. Pada konteks Indonesia, penelitian ini menggunakan laporan pemerintah tentang kontraterorisme dan wawancara dengan otoritas terkait. Hasil penelitian menunjukkan bahwa interaksi dua ideologi (agama dan nasionalisme) secara bersama-sama menciptakan kekuatan jihad kekerasan yang signifikan dan berkelanjutan di Iran selama Perang Irak- Iran dan Hamas Palestina melawan Israel dalam mencapai tujuan politik. Berbeda dengan praktik tersebut, Indonesia menggunakan nasionalisme dalam kebijakan kontraterorisme sebagai strategi melawan ideologi kekerasan bermotif agama. Artikel ini menunjukkan bahwa kebijakan kontraterorisme perlu lebih menekankan pada pemaknaan jihad tanpa kekerasan.Kata Kunci: agama; nasionalisme; jihad; penanggulangan terorisme